Comparison of Miniplate vs. 3D Plate Fixation in Mandibular Fractures: A Clinical Study - Muhammad Hamza Hashim, Usman ul Haq, Zainab Khalid, Amna Hassan, Yumna Shafqat Baig, Rubab Mumtaz, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Mandibular fractures constitute a significant portion of maxillofacial injuries, necessitating effective fixation methods to ensure optimal functional and aesthetic outcomes. This study aims to compare the clinical efficacy of traditional miniplate fixation with three-dimensional (3D) plate fixation in the treatment of mandibular fractures. A total of 100 patients with mandibular fractures were randomly assigned to two groups: Group A (miniplate fixation) and Group B (3D plate fixation)